Educational Robotics as a Factor in the Development of Network Interaction in the System of Engineering Training - Petr S. Cheremukhin; Aleksandr A. Shumeyko (National Research Mordova State University, 2018)
Introduction. Educational robotics is a new learning technology and an effective tool for training engineering staff. Networking of educational organizations and enterprises expands their potential in the system of level engineering training. The main idea of the article is to create and test a local model of an effective networked educational system in the context of federal and regional concepts and programs that would meet the development trends of modern society and at the same time would allow the preparation of schoolchildren for real participation in practical activities. Materials and Methods. We conducted a theoretical analysis of foreign and domestic literature. The method of scientific modeling, namely, the creation of a graphic hierarchical model was applied to develop an integrated system of engineering education for schoolchildren. When organizing the practical use of the model, pedagogical design, comparative analysis of verification works, sociological tools and criterial formative evaluation are used. Results. Authors made an attempt of systematization of subjects and forms of lifelong engineering education at the stages from preschool to higher, based on research conducted over six years. It is defined that the subject of inter-agency coordination network between participants of educational organizations. A tool to ensure continuity in the transition to a new level of education, and the implementation of interdisciplinary component pre-engineering education are interdisciplinary programs, in particular, robotics. Implementation of programs on robotics is carried out through curricular and extracurricular activities, additional education program, vacation employment and other forms of work, provided resources as the base of the organization and network partners. The author's summer program of the camp "Technosphere" was developed and approved with the day-time stay of children during the vacation period. The model of the Integrated System of Level Engineering Engineering for Schoolchildren was developed and introduced into the city's education system. Discussion and Conclusions.The system of level engineering training, which combines the levels of education, additional educational programs and the potential of network interaction, allows to optimize all directions and forms of organization of the educational process. As a result of the study, a model of an integrated system of level engineering training at the stage of pre-school and primary general education was developed.